2011
DOI: 10.48550/arxiv.1105.3894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unfolding mechanism and the free energy landscape of a single stranded DNA i-motif

Jens Smiatek,
Chun Chen,
Dongsheng Liu
et al.

Abstract: We present Molecular Dynamics simulations of a single stranded unprotonated DNA i-motif in explicit solvent. Our results indicate that the native structure in non-acidic solution at 300 K is unstable and completely vanishes on a time scale up to 10 ns. Two unfolding mechanisms with decreasing connectivity between the initially interacting nucleobases can be identified where one pathway is characterized as entropically more favorable. The entropic preference can be mainly explained by strong water ordering effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 32 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…19 that high temperature simulations at 500 K are able to reconstruct the unfolding pathway in good agreement to 300 K. Thus the main unfolding pathways can be also analyzed at higher temperatures which allows a significant decrease of simulation times to observe rare events 19 . It was also indicated that the global equi-librium structure of the hairpin configurations is shifted towards a fully unfolded strand at higher temperatures which was explained by a temperature-dependent entropy due to the interactions with the environment 18 . In this paper we want to study the transition mechanism between the hairpin configuration and a fully unfolded structure at high temperatures in detail.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…19 that high temperature simulations at 500 K are able to reconstruct the unfolding pathway in good agreement to 300 K. Thus the main unfolding pathways can be also analyzed at higher temperatures which allows a significant decrease of simulation times to observe rare events 19 . It was also indicated that the global equi-librium structure of the hairpin configurations is shifted towards a fully unfolded strand at higher temperatures which was explained by a temperature-dependent entropy due to the interactions with the environment 18 . In this paper we want to study the transition mechanism between the hairpin configuration and a fully unfolded structure at high temperatures in detail.…”
Section: Introductionmentioning
confidence: 98%
“…It was suggested that the choice of inappropriate collective variables may also cause significant deviations in the corresponding free energy landscapes due to the presence of hysteresis effects 17 . In recent publications 18,19 we have in detail discussed the corresponding stable conformations of a deprotonated i-motif as well as the possible transition pathways. The unfolding mechanism was mainly studied in terms of a principal component analysis [18][19][20] with the corresponding eigenvectors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations